Addressing Disability Inclusion in Nepal: Barriers and Actions (Quest Journal of Management and Social Sciences, 2024)
AbstractBackground: The discrepancy between global disability prevalence estimates and Nepal's 2021 census reveals significant challenges in promoting disability inclusion. This is due to unequal definitions and diagnostic criteria, with industrialised countries focusing on work-related impairments and social stigmas. Additionally, civil wars and natural disasters like the 2015 earthquakes make it difficult for Nepal's healthcare system to meet the diverse needs of people with disabilities.Objective: This study analyses the existing literature and identifies the current barriers and actions in promoting disability inclusion in Nepal.Methods: This study uses a literature review technique to analyse the publications on disability inclusion in Nepal from 2000 to 2024, focusing on challenges and interventions. It identifies key themes in research and practice, highlighting two issues: barriers to inclusion and actions to overcome them.Results: The findings reveal that inadequate infrastructure, limited rehabilitative programs, and restricted access to essential health and social rights exacerbate existing imbalances. Traditional beliefs in Nepal perpetuate discrimination and exclusion against disabled individuals due to negative perceptions and stigma. Disaster preparedness systems are often inadequate, and physical, environmental, communication, institutional, and economic barriers exacerbate these issues. Despite legislation, effective implementation and resource allocation remains weak. Coverage remains patchy despite efforts to mobilise NGOs and implement community-based rehabilitation initiatives.Conclusion: The Sustainable Development Goals should prioritise disability inclusion, prompting national and international stakeholders to prioritise disability needs. The International Classification of Functioning, Disability, and Health can improve data accuracy. People with disabilities should actively participate in policy creation for fair access and equality. Nepal must swiftly implement its constitution and health sector initiatives.Paper Type: Review PaperKeywords: Access, Disability, Diversity, Empowerment, Inclusion, Nepal